Marlene Dietrich i The Millionaire Waltz Queen. Językowo-muzyczne konstrukcje persony w muzyce popularnej - Gradowski, Mariusz; Konert-Panek, Monika (Załącznik Kulturoznawczy, 2020)
The paper adopts an interdisciplinary research perspective on popular music on the basis of the song The Millionaire Waltz by Queen. The main focus is placed on the key part of the song: the fragment in which the vocalist, Freddie Mercury, adopts German accent. This fragment is analyzed with reference to the concept of persona, both musical (A.F. Moore) and linguistic – as emphasized in the theory of style-shifting (A. Bell) and the third wave in sociolinguistics (P. Eckert). The analysis concentrates on the problem of the split between the performer, persona and protagonist in the song, as well as the artistic tension between projection and originality. The applied research tools and methods (Praat and Sonic Visualiser programs, as well as formal and auditive analises) lead to the conclusion confirming the popular in the analyzed song. His performance may be theorized as an example of Referee Design. Yet, some linguistic and musical aspects of this stylization suggest that this interpretation is not unambiguous. The complex character of the persona created by Mercury may be seen as an asset which gives rise to a wide spectrum of meanings (Marlene – German diva – diva), corresponding with Queen’s artistic tropes (stylization, cabaret, operetta, contrast, humor, nostalgia, queer) and maintaining the balance between reproduction and innovation. impression according to which Freddie Mercury imitates Marlene Dietrich.